1993
DOI: 10.1002/bjs.1800801117
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic screening for abdominal aortic aneurysm in an urban community

Abstract: As part of the Birmingham Community Aneurysm Screening Project, 3500 men aged 65-75 years from 20 urban general practices were invited for aortic ultrasonographic screening at their own general practitioner's surgery; 2669 (76.3 per cent) attended. Compliance rates varied between catchment areas, from 52.1 per cent for inner-city areas to 89.6 per cent for suburbs. Successful aortic imaging was achieved in 97.3 per cent of scans. Aortic diameter > 29 mm occurred in 219 patients (8.4 per cent) and 79 (3.0 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 33 publications
2
43
3
2
Order By: Relevance
“…McGregor et al19 proposed an infrarenal aorta diameter >30 mm. In a pilot study including 550 men between the ages of 65 and 75 years, Smith et al 13 proposed an infrarenal diameter of 29 mm because it was three standard deviations greater than the mean diameter of 21 mm. This definition has the advantage of being based on statistical data obtained in a relatively homogeneous, controlled population.…”
Section: Discussionmentioning
confidence: 99%
“…McGregor et al19 proposed an infrarenal aorta diameter >30 mm. In a pilot study including 550 men between the ages of 65 and 75 years, Smith et al 13 proposed an infrarenal diameter of 29 mm because it was three standard deviations greater than the mean diameter of 21 mm. This definition has the advantage of being based on statistical data obtained in a relatively homogeneous, controlled population.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings cast further doubt on a proposed association of AAA with chronic obstructive pulmonary disease. Several studies have reported a univariable association between AAA and chronic obstructive pulmonary disease, 13,14 and similar abnormalities in elastase activity have been observed in the two conditions. 11,12 However, in our first cohort, an association of chronic obstructive pulmonary disease with AAA of 4.0 cm or larger was lost after adjustment for number of years smoked, 2 and a Danish study has since reported similar findings.…”
Section: Commentmentioning
confidence: 99%
“…1,2,[11][12][13][14][15][16][17][18][19][20] Male gender and increasing age are consistently identified as non-modifiable risk factors for AAA. A positive family history of AAA is reported in 1% to 5% of patients (see below).…”
Section: Risk Factors For Abdominal Aortic Aneurysmmentioning
confidence: 99%